From Instability to Initiative: Navigating Editorial Challenges in the Formation of Independent News Portals in Indonesia - Ratnaningtyas, Rr. Pramesthi; Adiyanto, Wiwid (CHANNEL: Jurnal Komunikasi, 2025)
This study explores the editorial and organizational challenges faced by Indonesian journalists who, amid financial instability and professional dissatisfaction, choose to establish independent online news portals. Using a descriptive qualitative design grounded in phenomenological methodology, the research draws on the lived experiences of two senior journalists in Yogyakarta. Findings reveal that motivations for establishing independent media include dissatisfaction with low wages, editorial constraints, and weak media management. Despite limited human and financial resources, these journalists maintain their commitment to journalistic ideals while adapting to the demands of a competitive digital media environment. The study identifies three core challenges in establishing independent news outlets: human resources, funding, and marketing. It also highlights the role of media ecosystems in supporting operational viability, while emphasizing the compromises required to balance journalistic integrity with business sustainability. Anchored in the social responsibility theory of the media, this research contributes to scholarly discourse on media precarity, professionalism, and entrepreneurial journalism in the Global South. The findings suggest that, although independent journalism offers a path toward editorial autonomy, it remains vulnerable to structural, legal, and commercial pressures that continue to shape media practice in the digital era.